Reading Victorian poetry - Cronin, Richard, 1949- (Reading poetry., 2012)
Reading Victorian Poetry offers close readings of poems from the Victorian era by a renowned scholar. The selection includes a range of canonical and lesser known writers Skilfully conveys the breadth and diversity of nineteenth-century poetryOffers an ideal balance of canonical and less well-known writersAllows readers to explore the poetry of the Victorian era, through the eyes of one of the most renowned scholars in the fieldPoets covered include Matthew Arnold, Emily Brontë, Elizabeth Barrett Browning, Robert Browning, Lewis Carroll, A.H. Clough, G.M. Hopkins, Edward Lear, Christina Ro.